Business Plan : Starmoon Bakery / Nurul Nadiah Mohd Asri … [et al.] - Mohd Asri, Nurul Nadiah; Wan Naziron, Wan Natasha; Mohamad, Amira Syakira; Nazman, Daeng Kasturi; Bukhari, Muhammad Bashri (2021)
The purpose of this business plan is to secure long-term funding to open a Starmoon Bakery located at Starmoon Bakery, S/22 Lot 401(297 – A) Kg. Sireh, Jalan Kota Bharu Darul Naim, 15050, Kota Bharu, Kelantan. This business plan includes administration plan, marketing plan, operational plan, and financial plan. Furthermore, the name of this bakery shop which is “STARMOON Bakery” is come out from the creative mind by the partnership members and it shows that how we situating our products in customer's mind until they can remember our business name which is simple and effective to articulate including with the slogan “Love at First Bite”. Starmoon Bakery is focused on a partnership consisting of five partnership members that invest the same amount of capital which is RM 20,000 of each member and the total capital amounted to RM 100,000. Moreover, we had intended to set up this company through our long-term analysis and observation, because we can see a larger future prospect in this field. As for the business, we offer special and delicious cakes for the society at Kampung Sireh Kota Bharu. So, our survey concludes that we are going to provide the simple and special cakes to the Malaysian, which is well in the high quality of the product. Furthermore, our target customers are from all income levels and for all levels of age including children, teenagers and adults. Besides, to make it attractive and interesting, our bakery serves many types of cakes with different innovations, flavors and designs according to the customer requirements. So, the differences in types of cakes and taste will attract many kinds of people who love cakes. Moreover, the simple steps and high quality of ingredients give a lot of benefits to our business and we are highly confident that our market can be easily developed and spread in Malaysia. Finally, we expect Starmoon Bakery to be a well-known business nationally and to be able to offer more service from time to time. We also assume that the demand of our products which is cakes will increase every year as the increase in human population and be able to achieve our business goals with our business financial position statement. We also have our goal of getting the modal return within a short time and our current ratio would cover our liabilities and place the company in the highest comfort level. It is our pleasure to be the benchmark for those interested in starting a business.